2018
DOI: 10.1186/s12864-017-4394-y
|View full text |Cite
|
Sign up to set email alerts
|

Papain-like cysteine proteases in Carica papaya: lineage-specific gene duplication and expansion

Abstract: BackgroundPapain-like cysteine proteases (PLCPs), a large group of cysteine proteases structurally related to papain, play important roles in plant development, senescence, and defense responses. Papain, the first cysteine protease whose structure was determined by X-ray crystallography, plays a crucial role in protecting papaya from herbivorous insects. Except the four major PLCPs purified and characterized in papaya latex, the rest of the PLCPs in papaya genome are largely unknown.ResultsWe identified 33 PLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…Most of the enzymes will disappear with the ripening of fruits (Payasi, Mishra, Chaves, & Singh, ). For example, protease activities of figs and papayas are very high in the green fruits but become undetectable in softening ones (Liu et al, ; Zare et al, ). Pineapple plants produce bromelain in a different mode to other plants, as almost similar amounts of bromelain are present at the early and at the late stages of pineapple fruit development (Rajni, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the enzymes will disappear with the ripening of fruits (Payasi, Mishra, Chaves, & Singh, ). For example, protease activities of figs and papayas are very high in the green fruits but become undetectable in softening ones (Liu et al, ; Zare et al, ). Pineapple plants produce bromelain in a different mode to other plants, as almost similar amounts of bromelain are present at the early and at the late stages of pineapple fruit development (Rajni, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the enzymes will disappear with the ripening of fruits (Payasi, Mishra, Chaves, & Singh, 2009). For example, protease activities of figs and papayas are very high in the green fruits but become undetectable in softening ones (Liu et al, 2018;Zare et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, serine protease was the main protease class expressed in the fifth instar. High cysteine protease activities have already been detected in studies involving young larvae of Lepidoptera (Liu et al, ; Senthil‐Nathan, ) as well as the control of the gene expression of these enzymes, showing that there is an increase in the synthesis of serine proteases rather than the decrease of cysteine proteases in Tribolium castaneum (Lomate et al, ).…”
Section: Resultsmentioning
confidence: 95%
“…In this group, 181 members were identified. With A. thaliana , 31 proteases were reported [52], 33 in rice [17], 43 in rubber [53] and 33 in papaya [43]. Subfamilies of PLCPs (already described for A. thaliana [52] and rice [17]) were also identified.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid chromatography-mass spectrometry (LC-MS) is a powerful technique, which has been successfully used to study the properties of different wheat cultivars [2,3,39], plant development [40,41], and wheat responses to biotic [35,36] and abiotic stresses [37]. An LC-MS approach has been adopted in this study for characterization of all wheat proteases that were identified using Pfam identificators attributed to all the proteases with the use of profile hidden Markov model (HMMER) algorithm [42] that was previously successfully used for identification of proteins [43]. We performed classification of identified proteases.…”
Section: Introductionmentioning
confidence: 99%